Ventilator-associated pneumonia – An unwanted terror and a loathsome burden on the health-care cost in the recent era - Sharmila Gupta; Debarati Banerjee; Rituparna Haldar (Asian Journal of Medical Sciences, 2024)
Background: Ventilator-associated pneumonia (VAP) is defined as infection of lung parenchyma in patients exposed to invasive mechanical ventilation for at least 48 h. VAP is the second most common hospital-acquired infection with a mortality rate up to 40%. Aims and Objectives: To determine the microbiological profile of VAP-related samples, the demographic profile of patients, and associated risk factors. Materials and Methods: VAP-related samples including endotracheal tube tip, tracheal secretions, and bronchoalveolar lavage (BAL) fluid were collected from 73 patients during the study period from January 2023 to November 2023. Their blood samples were also collected for automated blood culture. Samples were processed as per standard protocol. Results: Out of the total patients, 60.31% were male and 39.68% were female. 61–80 years was the most commonly affected age group. The most commonly isolated micro-organism was Acinetobacter baumannii with the highest sensitivity to polymixin B and tigecycline. Associated blood culture positivity was maximum in patients whose samples of ET tube tip, tracheal secretions, and BAL fluid had isolated A. baumannii and Klebsiella pneumoniae. Two Candida albicans were isolated with sensitivities to voriconazole and amphotericin B. Many patients had associated septicemia. Endotracheal intubation and tracheal suction were the most common risk factors associated. Conclusion: As associated septicemia may increase the mortality rate manifold blood samples should also be collected in suspected VAP patients along with VAP-related samples for early detection of sepsis leading to better patient management.